2013
DOI: 10.1016/j.quaint.2011.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Investigating climate at the Upper Palaeolithic site of Kraków Spadzista Street (B), Poland, using oxygen isotopes

Abstract: Between 50,000 and 20,000 years ago, Europe experienced a series of rapid climate change events known as the Dansgaard-Oeschger cycles, which may have made areas of northern Europe more attractive for occupation by early modern humans at certain times than at others. This paper investigates when humans were occupying northern Europe in relation to these climatic changes at the archaeological site of Kraków Spadzista Street (B), by applying oxygen isotope analysis of mammoth tooth enamel carbonates (δ18O and δ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
12
1
Order By: Relevance
“…6 and 7). In the studied profiles we have not found data with so low MAT as those values determined by Pryor et al (2013) based on oxygen isotope analysis of the mammoth teeth at Krak ow Spadzista Street (B). The MAT VEG index estimated using the oxygen isotope compositions of calcite in rhizolites, gave reliable values of mean temperatures of growing seasons.…”
Section: Geochemical Indicescontrasting
confidence: 68%
“…6 and 7). In the studied profiles we have not found data with so low MAT as those values determined by Pryor et al (2013) based on oxygen isotope analysis of the mammoth teeth at Krak ow Spadzista Street (B). The MAT VEG index estimated using the oxygen isotope compositions of calcite in rhizolites, gave reliable values of mean temperatures of growing seasons.…”
Section: Geochemical Indicescontrasting
confidence: 68%
“…5) and Poland (Kraków Spadzista Street,~24 cal ka BP; Pryor et al, 2013;Fig. 5), with MAT values ranging between 0.5°C and 1°C, respectively.…”
Section: The Ajoie Region In the European Climatic Context During Mismentioning
confidence: 99%
“…Numbers 3, 4, 6, 7, 8 and 9 refer to MIS3 localities shown in Fig. 5 (according to Tütken et al, 2007;Arppe and Karhu, 2010;Fabre et al, 2011;Pryor et al, 2013). (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.…”
Section: The Ajoie Region In the European Climatic Context During Mismentioning
confidence: 99%
“…This kind of unusual dietary stress probably also affected Zimbabwe's Loxodonta population during major droughts in the 1980s, and probably also affected cold-period Mammuthus in Europe. Pryor et al (2013) concluded that the Krak ow-Spadzista Street B mammothdominated Gravettian archaeological assemblage was created "in the context of an extremely cold climate," 4e9 C colder than the present climate at the site, creating "environmental conditions… relatively not very pleasant for humans" (Lanczont et al, 2014 [in press]), probably leading to sustained or recurring dietary insufficiencies that would help explain the numerous abnormalities in bones and teeth documented by Krzemi nska and colleagues (Krzemi nska, 2008;Krzemi nska and Wojtal, 2014;Krzemi nska and Wę dzicha, 2015;Krzemi nska et al, 2015) and Leshchinskiy (2012).…”
Section: Discussionmentioning
confidence: 99%